2005
DOI: 10.2165/00128071-200506030-00001
|View full text |Cite
|
Sign up to set email alerts
|

Managing Adverse Events Associated with Botulinum Toxin Type A

Abstract: Botulinum toxin A (BTXA) has become a widely used drug in cosmetic dermatology, not only to treat focal hyperhidrosis but also hyperkinetic facial lines, platysma bands, décolleté bands, and other skin features. The spectrum of possible adverse effects of BTXA is broad but fortunately those that have been observed with cosmetic use of this product are generally mild and transient. The major tools for preventing adverse effects from BTXA are knowledge and skill. Use of correct injection techniques is mandatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(55 citation statements)
references
References 55 publications
0
54
0
1
Order By: Relevance
“…Blepharoptosis (upper eyelid droop) is uncommon (1% to 5%) (12,16). It is usually unilateral and marked at the end of the day with muscle fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…Blepharoptosis (upper eyelid droop) is uncommon (1% to 5%) (12,16). It is usually unilateral and marked at the end of the day with muscle fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous reliable, well-designed double-blind studies concerning the clinical application of botulinum toxins [75, 80, 93, 94] have confirmed beyond doubt that toxin administration under clinical supervision is fairly safe. The de facto confirmation of the safety of such interventions advocating wider, clinically supervised use of botulinum neurotoxins is reinforced by the existence of a strong theoretical background.…”
Section: Discussionmentioning
confidence: 99%
“…Although the pathology is manifested in the muscles, the causes of spasticity must be attributed to central nervous system damage. This damage disrupts the equilibrium between inhibitory and excitatory signals, resulting in increased muscle stimulation [80, 81]. The clinical features of muscle spasticity are mainly characterized by pain, permanent muscle shortening and lack of voluntary movements.…”
Section: Botulinum Neurotoxins and Rehabilitation Medicinementioning
confidence: 99%
“…6 The diffusion of the different drugs seems to be dependent on concentration. 7 BTX-A has an excellent safety profile 8 and has been used extensively for facial rejuvenation with a focus on hyperkinetic wrinkles and to improve facial wound healing after surgery.…”
Section: Botulinum Toxin Type a (Btx-a)mentioning
confidence: 99%